Current practices in offshoring and reshoring (Pearson, 2014)
The CSCMP Research Strategies Committee (RSC) sees significant value in systematic research to better understand location decision trends and the key factors driving them. If your organization is concerned about where to locate manufacturing operations and whether to revisit offshoring decisions, this CSCMP research can be an invaluable resource! Founded in 1963, the Council of Supply Chain Management Professionals (CSCMP) is the preeminent worldwide professional association dedicated to the advancement and dissemination of research and knowledge on supply chain management. With over 8,500 members representing nearly all industry sectors, government, and academia from 67 countries, CSCMP members are the leading practitioners and authorities in the fields of logistics and supply chain management.